2014
DOI: 10.1093/jscr/rju031
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent wound dehiscence and small bowel herniation following Caesarean section in a woman with hidradenitis suppurativa

Abstract: Caesarean wound dehiscence that is severe enough to result in bowel herniation is exceptionally rare. This case describes a woman who experienced wound dehiscence following each of her two Caesarean sections, with bowel herniation present in the second case. The contribution of her comorbid hidradenitis suppurativa will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There has been one other case report published which describes wound dehiscence following caesarean section in a female with HS, with multiple other comorbidities including obesity, gestational diabetes, and current smoker. The case report described that wound dehiscence was common following excision of HS lesions and as a result suggested that HS was the cause for the patient's postoperative complications [5].…”
Section: Discussionmentioning
confidence: 99%
“…There has been one other case report published which describes wound dehiscence following caesarean section in a female with HS, with multiple other comorbidities including obesity, gestational diabetes, and current smoker. The case report described that wound dehiscence was common following excision of HS lesions and as a result suggested that HS was the cause for the patient's postoperative complications [5].…”
Section: Discussionmentioning
confidence: 99%
“…Skin changes related to HS near surgical incisions could increase rates of wound dehiscence, perhaps due to subacute bacterial infections secondary to HS. A case report describes recurrent wound dehiscence after Cesarean section and postulates that HS may have been a factor, but there is little other literature on the topic [ 19 ].…”
Section: Discussionmentioning
confidence: 99%